The Relationship between the Level of Compliance in the Physiotherapy Program and the Functional Ability of Patients with Genu Osteoathritis at Dr. Moewardi Hospital - Farid Rahman; Hafiz Arief Nur’ana; Dinik Ayundya Marlis; Ilham Setya Budi; Dinda Ayudya Puspitaningrum (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Genu Osteoathritis is a degenerative disease characterized by damage to articular cartilage so that it can cause symptoms of stiffness and pain in the knee joint that will affect the functional ability of adherence or also called compliance is an important component in the physiotherapy program, especially exercise therapy for patients, because adherence greatly determines the success rate of the outcomes compiled by the physiotherapist. The purpose of this study was to determine the relationship between the level of patient compliance in the physiotherapy program with the functional abilities of patients with genu osteoathritis. This research method used a correlational research method with cross sectional approach. Namely the research method used to find the relationship between the independent variable and the dependent variable. The population in this study was 30 people. The measurement of functional ability using a questionnaire is the Knee Injury and Osteoathritis Outcome Score (KOOS) and to measure the respondent's level of compliance using the Exercise Adherence Rating Scale (EARS). The results of the study were analyzed using the product moment correlation test and the p-value was 0.347. So it can be concluded that there is no corelation between the level of adherence with the functional abilities of patients with genu osteoathritis in RSUD Dr. Moewardi.